2018
DOI: 10.1016/j.bbabio.2018.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of 2-methoxy-1,4-naphtoquinone by mitochondrially-localized Nqo1 yielding NAD+ supports substrate-level phosphorylation during respiratory inhibition

Abstract: Provision of NAD for oxidative decarboxylation of alpha-ketoglutarate to succinyl-CoA by the ketoglutarate dehydrogenase complex (KGDHC) is critical for maintained operation of succinyl-CoA ligase yielding high-energy phosphates, a process known as mitochondrial substrate-level phosphorylation (mSLP). We have shown previously that when NADH oxidation by complex I is inhibited by rotenone or anoxia, mitochondrial diaphorases yield NAD, provided that suitable quinones are present (Kiss G et al., FASEB J 2014, 28… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 80 publications
0
9
0
Order By: Relevance
“…Unfortunately, we saw the Complex I bypass activity of Me-MNQ in cortical astrocytes but not neurons, as was the case for idebenone. This finding suggests that the bypass activity of naphthoquinone derivatives may also require NQO1-reducing activity, as MNQ is a preferred NQO1 substrate (Ravasz et al, 2018). Unlike idebenone, we found that the naphthoquinones MNQ and Me-MNQ increase antimycin A-insensitive oxygen consumption, likely due to superoxide generation, which may limit their therapeutic potential.…”
Section: Discussionmentioning
confidence: 67%
“…Unfortunately, we saw the Complex I bypass activity of Me-MNQ in cortical astrocytes but not neurons, as was the case for idebenone. This finding suggests that the bypass activity of naphthoquinone derivatives may also require NQO1-reducing activity, as MNQ is a preferred NQO1 substrate (Ravasz et al, 2018). Unlike idebenone, we found that the naphthoquinones MNQ and Me-MNQ increase antimycin A-insensitive oxygen consumption, likely due to superoxide generation, which may limit their therapeutic potential.…”
Section: Discussionmentioning
confidence: 67%
“…To our knowledge, this is the first time that endogenous CoQ has been shown to regulate NOX4 activity, which is in agreement with previous findings for synthetic quinone compounds and NQO1 overexpression [ 18 ]. Importantly, although NQO1 is known to regulate mitochondrial function, its localization on the mitochondrial membrane remains controversial [ [49] , [50] , [51] , [52] , [53] ]. While NQO1 can be detected in mitochondria isolated from multiple mouse tissues, it was not found in mitochondria in a human cell line [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…The decrease in NAD + provision to KGDHC with the aim of diminishing mSLP is the strategy followed by including β-hydroxybutyrate in the media (supporting NADH generation by β-hydroxybutyrate dehydrogenase) relying on the fact that KGDHC activity is important for mSLP [7]. Provision of NAD + to KGDHC in the absence of oxidative phosphorylation occurs through mitochondrially-localized diaphorases, [17] such as mitochondrially-localized NQO1 [18]. The effect of 2-KB inhibiting pyruvate oxidation has been published before [19], albeit this was only observed at very high 2-KB concentrations (20 mM).…”
Section: Discussionmentioning
confidence: 99%